CONDIÇÕES DE TRABALHO, DOR MUSCULOESQUELÉTICA E ÍNDICE DE CAPACIDADE PARA O TRABALHO DA EQUIPE DE ENFERMAGEM - Lima, Ana C. S. D.; Magnago, Tânia B. D. S.; Prochnow, Andrea; Amthauer, Camila (Salão do Conhecimento, 2013)
Resumo